If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3d + -8)(3d + -8) = 0 Reorder the terms: (-8 + 3d)(3d + -8) = 0 Reorder the terms: (-8 + 3d)(-8 + 3d) = 0 Multiply (-8 + 3d) * (-8 + 3d) (-8(-8 + 3d) + 3d * (-8 + 3d)) = 0 ((-8 * -8 + 3d * -8) + 3d * (-8 + 3d)) = 0 ((64 + -24d) + 3d * (-8 + 3d)) = 0 (64 + -24d + (-8 * 3d + 3d * 3d)) = 0 (64 + -24d + (-24d + 9d2)) = 0 Combine like terms: -24d + -24d = -48d (64 + -48d + 9d2) = 0 Solving 64 + -48d + 9d2 = 0 Solving for variable 'd'. Factor a trinomial. (8 + -3d)(8 + -3d) = 0Subproblem 1
Set the factor '(8 + -3d)' equal to zero and attempt to solve: Simplifying 8 + -3d = 0 Solving 8 + -3d = 0 Move all terms containing d to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3d = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -3d = 0 + -8 -3d = 0 + -8 Combine like terms: 0 + -8 = -8 -3d = -8 Divide each side by '-3'. d = 2.666666667 Simplifying d = 2.666666667Subproblem 2
Set the factor '(8 + -3d)' equal to zero and attempt to solve: Simplifying 8 + -3d = 0 Solving 8 + -3d = 0 Move all terms containing d to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3d = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -3d = 0 + -8 -3d = 0 + -8 Combine like terms: 0 + -8 = -8 -3d = -8 Divide each side by '-3'. d = 2.666666667 Simplifying d = 2.666666667Solution
d = {2.666666667, 2.666666667}
| 7x+13(10x-12)=255 | | 7x-21x^2/7x | | 9y^2-21y+12= | | (u+v)(u+v)=0 | | y^5+18y^3+81y^1=0 | | 7x-21x^2/7x=0 | | 2160=(n-2)180 | | 4.20*3.15=u | | 4.20*0.75=u | | 36-(8-X)=X+2-(5-X) | | (r+(4/7))(r-(4/7))=0 | | (r+4/7)(r-4/7)=0 | | (4-9x)(4+9x)=0 | | (6a-8b)(6a+8b)=0 | | 2x+-4.9=-3.6 | | In(x-1)+In(x+2)=1 | | x^3+0x^2-67x+126=0 | | (10h+2)(10h-2)=0 | | 5-26/5b=5b/b+1 | | 10y^2-28y+18= | | 2x+-4.6=-3.6 | | x^3-67x+126=0 | | g=660+325 | | 0.2/8.4 | | (9x^2+10x+4)(4x+1)=0 | | y=660+325+g | | h=529+-16t^2 | | 8.4/0.2 | | 2x-4.3=-3.9 | | h=529-16t^2 | | 16-(8-x)=0.85-20 | | (2s+1)(4s^2-2s+1)=0 |